Substantial Global Radial Variations of Basalt Content Near the 660‐km Discontinuity - Shangqin Hao; S. Shawn Wei; Peter M. Shearer (AGU Advances, 2024)
Abstract Mid‐ocean ridges generate basalt and harzburgite, which are introduced into the mantle through subduction as a mechanical mixture, contributing to both lateral and radial compositional heterogeneity. The possible accumulation of basalt in the mantle transition zone has been examined, but details of the mantle composition below the 660‐km discontinuity (hereafter d660) remain poorly constrained. In this study, we utilize the subtle waveform details of S660S, the underside shear‐wave reflection off the d660, to interpret the seismic velocity, density, and compositional structure near, and particularly below, the d660. We identify a significant difference in S660S waveform shape in subduction zones compared to other regions. The inversion results reveal globally enriched basalt at the d660, with a notably higher content in subduction zones, consistent with the smaller impedance jump and S660S peak amplitude. The basalt fraction decreases significantly to less than 10% near 800‐km depth, forming a global harzburgite‐enriched layer and resulting in a steep seismic velocity gradient just below the d660, in agreement with 1D global reference models. The striking compositional radial variations near the d660 verify geodynamic predictions and challenge the applicability of homogeneous radial compositional models in the mantle. These variations may also affect the viscosity profile and, consequently, the dynamics at the boundary between the upper and lower mantle.